2010
DOI: 10.4314/swj.v3i2.51800
|View full text |Cite
|
Sign up to set email alerts
|

Pollution assessment of the impact of coastal activities on Lagos lagoon, Nigeria

Abstract: Tributaries of Lagos lagoon at Oworonsoki and Ebute Meta, known for residential and commercial activities were studied to assess the impact of coastal activities on Lagos lagoon. The mean levels of some parameters at the activity points gave evidences of pollution in the studied areas. The mean values for dissolved oxygen was 2.09 mg/l and chemical oxygen demand was 267 mg/l at Oworonsoki, while at Ebute meta, mean values for same parameters at the activity points were 1.16 mg/l and 786.5 mg/l respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 1 publication
(1 reference statement)
2
13
0
Order By: Relevance
“…Further, Table 1 presents data on the state and severity of building collapse in Nigeria. Table 1 suggest that residential buildings are more prone to collapse in Nigeria, adding to the intractable housing shortages experienced in Nigeria [13][14][15]. Thus the potential for investment accumulation in Nigeria is being lost to building collapse.…”
Section: Review Of the State And Severity Of Building Collapse In Nigmentioning
confidence: 99%
“…Further, Table 1 presents data on the state and severity of building collapse in Nigeria. Table 1 suggest that residential buildings are more prone to collapse in Nigeria, adding to the intractable housing shortages experienced in Nigeria [13][14][15]. Thus the potential for investment accumulation in Nigeria is being lost to building collapse.…”
Section: Review Of the State And Severity Of Building Collapse In Nigmentioning
confidence: 99%
“…Pollution studies have revealed elevated levels of Pb, Cr, Ni, V, and Zn in Port Harcourt and Warri sediments and some species of fauna, suggesting inputs from petroleum exploration and exploitation (Kakulu & Osibanjo, 1988;Kakulu & Osibanjo, 1992). Consequently, the concentration of these metals in Nigerian coastal waters and sediment are of great concern, warranting the need for periodic sampling and analyses of both water and water resources in order to monitor the pollution and productivity status of the marine ecosystem and compare the data with international standards (Ajao et al, 1996;Nubi et al, 2008). This paper reports the results of a study aimed at evaluating the trace elements such as Cd, Pb, Mn, Zn, Cu, Fe and Cr in different species of finfish from coastal waters at Badagry, Nun River, Sombreiro River, and Cross River.…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene products can lead to suffocation of aquatic animals which mistakenly swims into them and when swallowed may result is blockages of tracts and eventually death. Nubi et al (2008) in their study, reported that most of the wastes found in these dumps are persistent (non-biodegradable) in the environment, and continuously leach heavy metal into the water body.…”
Section: Acute Toxicity Of Leachates On Brackish Water Shrimp (Palaeomentioning
confidence: 99%
“…The high population density and lack of regulatory framework has made coastal dumping a normal occurrence.Coastal pollution, and the overexploitation of natural resources, are global problems but are particularly severe in areas of high population density and those adjacent to semi-enclosed and shallow seas (Evans et al, 1995). Coastal dumps may results in leaching of toxicants and release of debris into water resulting the changes in water chemistry (Nubi et al, 2008) , loss of aesthetics and sometimes fish kills due to entanglement and asphyxiation by plastic materials (Derraik, 2002).Waste in coastal area deforms beautiful seaside landscape and the slow rate of degradation rate of wastes such as plastic is of environmental concern as well (Rezazadeh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%